Concomitant necrotizing encephalitis and granulomatous meningoencephalitis in four toy breed dogs - Nessler, Jasmin Nicole; Oevermann, Anna; Schawacht, Marina; Gerhauser, Ingo; Spitzbarth, Ingo; Bittermann, Sophie; Steffen, Frank; Schmidt, Martin Jürgen; Tipold, Andrea (Frontiers in Veterinary Science, 2022)
The term “meningoencephalitis of unknown origin” (MUO) describes a group of different encephalitides in dogs in which no infectious agent can be identified and a multifactorial etiology is suspected. Among others, genetic factors and unknown triggers seem to be involved. Included are necrotizing leukoencephalitis (NLE), necrotizing meningoencephalitis (NME), and granulomatous meningoencephalitis (GME). In this case series, we describe the histopathological findings of four toy breed dogs with focal or multifocal necrotizing encephalitis and mainly lymphocytic perivascular infiltrates on histopathological examination. At the same time, however, in all dogs, focal or multifocal high-grade angiocentric granulomatous inflammatory lesions were evident with focal histiocytic perivascular infiltrates in the brain. The former changes are typical for NLE and NME. In contrast, the latter changes are indicative of GME. This case series shows that the boundaries between the necrotizing and granulomatous variants of MUO might be smooth and suggests that NLE, NME, and GME are not as distinct as previously described. This finding could be a crucial piece of the puzzle in the study of the pathogenesis of MUO as individual susceptibility and specific triggers could be responsible for the manifestation of the different MUO subtypes.